Your phrasing of the question makes it invalid. The way you wrote it, it reads:
y = 3x + 2
y = 2x = 1
If that latter statement is true, then we are told that y = 1 and x = 1/2. This does not make sense though, as the it doesn't meet the conditions of the original statement, y = 3x + 2.
Chat with our AI personalities
3x+56 = 2x+4 3x-2x = 4-56 x = -52
3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20
-3x + (-18) = 2x + 7 +18 +18 -3x = 2x +25 -2x -2x -5x = 25 ----- ----- -5 -5 x=-5 *------- equals a division line
2x + 2 = 3x - 57 = x
2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2